RECURRENT LIVER ECHINOCOCCOSIS AS AN INDICATOR OF THE QUALITY OF PRIMARY SURGICAL TREATMENT AND PREVENTION IN AN ENDEMIC REGION (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Recurrent liver echinococcosis remains one of the most difficult problems in abdominal surgery in endemic regions. Re-identification of echinococcal cysts after a previously performed operation may be associated with different mechanisms: residual lesion, implantation relapse, or true re-invasion. However, in clinical practice, these variants are often combined under the general term "recurrent", which makes it difficult to objectively assess the quality of initial treatment, choose a repeat surgical approach, and determine preventive priorities. In this regard, it is an urgent task to develop a tool that allows for the differentiation of repeated forms of liver echinococcosis based on available clinical and anatomical criteria.